Research progress on durability of marine concrete under the combined action of Cl− erosion, carbonation, and dry–wet cycles - Zhang, Maohua; Xu, Ronghua; Liu, Ke; Sun, Shanghui (Reviews on advanced materials science, 2022)
Marine concrete is a kind of construction material which is seeking its growing application in marine engineering. However, the marine concrete structures are exposed to aggressive environment and harmful ions. Therefore, it is crucial to improve the durability of marine concrete. The concrete structure located in the tidal zone is subjected to the dry–wet cycles caused by tidal action, chloride ion (Cl ) erosion in seawater, and CO erosion in air. When these factors work together, they cause great damage to the marine concrete structure. In view of the three environmental factors, namely, Cl erosion, carbonation, and dry–wet cycles, taking fly ash, fibers, and nanomaterials as examples, this article expounds the research status of durability of marine concrete, introduces the latest research progress, the addition of fibers, fly ash, and nanomaterials can improve the Cl corrosion resistance and dry–wet cycles resistance of marine concrete, while the addition of fly ash is unfavorable for carbonation resistance. And the future development trend of marine concrete is prospected.